Sense and Second-Degree Murder - Price, Tirzah (New York : HarperTeen, 2022)
Eighteen-year-old aspiring chemist Elinor Dashwood and her younger sister Marianne, a budding detective, work together to solve the mystery of their father's murder. Includes author's note.
Keywords: Murder -- Juvenile fiction; Opium -- Juvenile fiction; Sisters -- Juvenile fiction; Great Britain -- Juvenile fiction. -- History -- Regency, 1811-1820; Murder -- Fiction; Opium -- Fiction; Sisters -- Fiction; Characters in literature -- Fiction; Mystery and detective stories; Great Britain -- Fiction. -- History -- Regency, 1811-1820; Novels; Detective and mystery fiction; Historical fiction